My Sister's Silent World - Arthur, Catherine; Talbot, Nathan (Chicago : Childrens Press, 1979)
A child describes her sister's hearing problem and the family's birthday visit to the zoo.
Keywords: Deaf -- Fiction; Brothers and sisters -- Fiction; Family -- Fiction